The Efficacy of Levobupivacaine Hydrochloride–Dexamethasone Infiltration for Post-Tonsillectomy Pain in Adults. Issue 7 (October 2015) - Bayram, Ali; Doğan, Murat; Cihan, Celalettin; Karataş, Duran; Gökahmetoğlu, Günhan; Özcan, Ibrahim
Abstract : Objective: The aim of the study is to evaluate the efficacy of peritonsillar infiltration of a levobupivacaine hydrochloride and dexamethasone combination for post-tonsillectomy pain in adult patients. Methods: A total of 40 patients were included in this double-blind, randomized, and placebo-controlled study. The patients were equally randomized into 2 groups by means of sealed envelopes. The study group (SG) received peritonsillar levobupivacaine hydrochloride and dexamethasone infiltration and the control group (CG) received peritonsillar saline infiltration. Pain scores at the second, fourth, eighth, 12th, 16th, and 24th hours and the second to seventh days after operation were recorded by the patients in each group using a visual analog scale. Duration of surgery and the total amount of blood loss during the surgery were also recorded for each patient. Results: All pain scores in the SG were lower than those in the CG; however, the difference was significant at the second, 12th, and 16th hours, and the second and third day ( P  < 0.05). Postoperative morbidity parameters, including otalgia, nausea, vomiting, fever, halitosis, and bleeding were similar between the 2 groups. Total amount of analgesic consumption in the SG was significantly lower than in the CG on each day of the week after tonsillectomy. Conclusions: Peritonsillar infiltration of a levobupivacaine hydrochloride and dexamethasone combination may provide pain reduction and decrease analgesic consumption in the postoperative period after adult tonsillectomy.